Synthesis and characterisation of nanostructured tio2 for photocatalytic applications - Albetran, Hani Manssor Mohammed (Curtin University, 2016)
This thesis focused on the synthesis and characterisation of nanostructured TiO2 mainly for photocatalytic application, as well as other applications in general. Electrospun titania nanofibers and anodised titania nanotubes were synthesised and characterised using different analytical techniques. Effect of atmospheric air and argon, and ion implantation on the crystallization kinetics, anatase-to-rutile transformation, and band gaps were investigated using in-situ high temperature synchrotron radiation diffraction (SRD) from room temperature to 900 °C.